2021
DOI: 10.3390/en14185617
|View full text |Cite
|
Sign up to set email alerts
|

Heating Performances of a Large-Scale Factory Evaluated through Thermal Comfort and Building Energy Consumption

Abstract: Workshops with a large area and a high ceiling height without compartments, such as large-scale assembly factories, have an uneven thermal comfort during heating, making it difficult to establish an effective heating strategy. In this study, we evaluate the heating performance of a large-scale factory based on thermal comfort and energy flow and discuss effective heating methods. In addition, an analysis of the heating performance of a large-scale factory is attempted for the first time. To analyze the heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…24 The ADPI selection guide is different in cooling and heating operation modes. 13,54 In the future, in order to improve the applicability of CMT, the influence of supply air temperature difference on throw length needs to be corrected.…”
Section: ) Analysis Of Airflow Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The ADPI selection guide is different in cooling and heating operation modes. 13,54 In the future, in order to improve the applicability of CMT, the influence of supply air temperature difference on throw length needs to be corrected.…”
Section: ) Analysis Of Airflow Patternmentioning
confidence: 99%
“…For heating conditions, thermal air floating at low wind velocity would lead to vertical stratification of room temperature, resulting in 'warm head-cool feet' discomfort. 13 Furthermore, some studies have shown that a lower air supply would reduce indoor pollutant removal efficiency. Indoor health problems caused by insufficient air supply exist in hospitals, 14,15 office buildings, 16,17 residences 18 and public places.…”
Section: Introductionmentioning
confidence: 99%